2010
DOI: 10.1002/lsm.20946
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Er:YAG laser and piezoelectric osteotomy: An animal study in sheep

Abstract: Er:YAG laser osteotomy can successfully be used in long bones with a depth of up to 22 mm, thus challenging the dogma of adverse effects of laser osteotomy due to thermal or other damages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…10,11,14,15,18,22,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In an in vitro study by Müller 9 comparing osteotomies created in various ways, showed that Piezosurgical (Mectron) osteotomies were morphologically similar to those created with conventional drills or microsaws. Romeo et al 36,45 in another in vitro study, compared the Er:YAG laser, a Piezoelectric device (Mectron), a high-speed handpiece using Lindemann burs and round diamonds, and a low-speed handpiece using round stainless steel burs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11,14,15,18,22,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] In an in vitro study by Müller 9 comparing osteotomies created in various ways, showed that Piezosurgical (Mectron) osteotomies were morphologically similar to those created with conventional drills or microsaws. Romeo et al 36,45 in another in vitro study, compared the Er:YAG laser, a Piezoelectric device (Mectron), a high-speed handpiece using Lindemann burs and round diamonds, and a low-speed handpiece using round stainless steel burs.…”
Section: Discussionmentioning
confidence: 99%
“…1,10,[12][13][14][15][16][17][18][19] Hollstein et al 20 examined the differences in performance of 5 types of Piezosurgical devices, specifically the duration of osteotomies, surface roughness, osteoblast vitality, and osteotomy site micromorphology. However, 3 of those 5 devices were manufactured by Mectron (the Piezosurgery 3, Piezotom 2, and Piezosurgery Medical).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their great manoeuverability in the recent past, lasers and high-pressure water jets have been evaluated. However, even though results especially for certain laser systems were promising [24], in daily routine oscillating and ultrasound based systems are still preferred by surgeons. Osteotomy speed and depth control using saw blades is still unrivalled.…”
Section: Discussionmentioning
confidence: 99%
“…However, low heat production risk of erbium makes it superior regarding thermal necrosis of the living tissues like dental pulp [83] and bone marrow [84].…”
Section: Dentistrymentioning
confidence: 99%